Effect of cysteine using Fenton processes on decolorizing different dyes: a kinetic study. Issue 1 (2nd January 2022) - Nicodemos Ramos, Márcio Daniel; Sousa, Larissa Aquino; Aguiar, André
ABSTRACT: Amino acid cysteine has been used as reducing mediator with the aim of improving dye degradation by homogeneous Fenton processes (Fe 2+ /H2 O2 and Fe 3+ /H2 O2 ). Through its known Fe 3+ -reducing activity, this amino acid can enhance the production of reactive oxygen species as HO (hydroxyl radical) and its pro-oxidant properties have been verified while decolorizing diverse dyes in the present work. Its presence enhanced decolorization of Methyl Orange, Phenol Red, Safranin T, Rhodamine B, Reactive Black 5 and Reactive Yellow 2, mainly in reactions initially containing Fe 3+ as a catalyst (Fe 3+ -reactions). E.g. Fe 3+ /H2 O2 and Fe 3+ /H2 O2 /cysteine systems decolorized 27% and 44% of Phenol Red after 60 min, respectively. A kinetic modeling analysis has revealed that 1st-order and mainly 2nd-order kinetic models were well fitted to both Fe 2+ - and Fe 3+ -reactions data. Improvements in reaction rate constants have been observed by adding cysteine. In experiments performed at varied temperatures, it was found a decrease in activation energy ( Ea ) due to cysteine addition while decolorizing Safranin T: Ea decreased from 104.6 to 88.9 kJ mol −1 for Fe 3+ -reactions and from 81.0 to 52.2 kJ mol −1 for Fe 2+ -reactions. Therefore, it was found that cysteine decreases the energy barrier so as to improve Fenton-based decolorization reactions. GRAPHICAL ABSTRACT: UF0001